Interim analysis of a phase II study of nivolumab/ipilimumab plus cabozantinib in patients with unresectable advanced melanoma - Pecora, Andrew L; Rapisuwon, Suthee; Chen, Kevin; Gardner, Kellie; Cramer, Gayle; Blair, Danielle; Avergas, Amy; Swanson, Nicole; Ahn, Jaeil; Atkins, Michael B. (Journal of clinical oncology, 2023)
9563Background: Nivolumab/ipilimumab (Nivo/Ipi) is a standard therapy in patients with unresectable stage III/IV melanoma, demonstrating an objective response rate (ORR) of 58% and 12-month progression free survival (PFS) rate of 49% [Wolchok J, NEJM 2017]. c-MET/VEGFR2 inhibition with cabozantinib (Cabo) has modest clinical activity in melanoma and can augment antitumor immunity by increasing CD8+ Tcell and macrophage tumor infiltration, decreasing intratumoral regulatory Tcell levels, and increasing tumor cell MHC antigen presentation. Nivo/Ipi plus Cabo showed clinical activity and acceptable toxicity profile in GU malignancies [Apolo AB, JCO 2020]. We performed a study of Nivo/Ipi plus Cabo in advanced melanoma patients aimed at improving efficacy. Methods: We conducted a multicenter phase II study of induction Nivo 3mg/kg IV and Ipi 1mg/kg IV and Cabo 40mg PO daily every 3 weeks for 4 cycles, followed by Nivo 480mg IV plus Cabo 40mg PO daily every 4 weeks for up to 2 years, until disease progression or unacceptable toxicity/patient withdrawal. Patients with unresectable stage III/IV melanoma and no prior anti-PD-1 or CTLA-4 exposure (unless in adjuvant setting > 6 months since last dose) were included. Uveal melanoma excluded. Primary endpoint was 12-month PFS rate. Secondary endpoints included ORR, overall survival (OS), and adverse events (AEs). Interim analysis was preplanned after first 14 subjects were evaluated in a Simon 2 stage design (goal >8 subjects 12-month progression free). Results: As of 1/2023, 14 subjects were enrolled across three cancer centers within the Georgetown-Lombardi Comprehensive Cancer Center Consortium. Median age 66.5 years, all stage IV disease, 10 with cutaneous primary site, 5 with elevated LDH, and 6 with BRAF V600 mutant tumor. Median follow up was 10.6 mos. 12-month PFS rate was 30% (3/10 evaluable subjects); 3 subjects pending PFS evaluation; median PFS 10.3 mos. ORR was 46% (6/13 evaluable subjects) with 2 CR, 4 PR, and 1 SD. Responders had cutaneous (5) or unknown (1) primary sites. 9 patients were alive at last follow up. 12-month OS rate was 67% (6/9 evaluable subjects). Reasons for treatment discontinuation included AEs (4), patient withdrawal (1), and disease progression (6). 3 subjects remain on study drug(s). Treatment related AEs (TRAEs) were observed in 13 subjects; 9 experienced a grade 3-4 TRAE (most frequent were elevated AST/ALT 29% and hypokalemia 14%). Most frequent grade 2 TRAEs were diarrhea (35%) and palmar-planter-erythrodysesthesia (29%). No treatment related deaths occurred. Conclusions: Clinical activity was observed with Nivo/Ipi plus Cabo in advanced melanoma but did not meet the predefined threshold to advance to the second stage of enrollment. TRAE profile was similar to prior reports. Biomarker analyses are planned to identify patient profiles associated with particular benefit from this regimen. Clinical trial information: NCT04091750.